1982
DOI: 10.1111/j.1939-0025.1982.tb01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nuclear war threat on children and teenagers: Implications for professionals.

Abstract: Interview studies of youngsters are cited as evidence of their pervasive awareness of the possibility of nuclear cataclysm. It is suggested that the nuclear threat is a contributing factor in anxiety and other disorders noted among these youth. The role of mental health and other professionals in educating and guiding youngsters, and in working with them to reduce the anxiety and alleviate its causes, is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 2 publications
1
52
1
Order By: Relevance
“…Although correlational relationships do not validate the causal implications made by Escalona (1982). Schwebel (1982), Mack (1982, 1983), and Dodds (1983), these are necessary conditions for the validation of the relationships. Beginning with elementary-age childre, longitudinal data to assess the causal implications seem warranted and positively supported by these findings.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although correlational relationships do not validate the causal implications made by Escalona (1982). Schwebel (1982), Mack (1982, 1983), and Dodds (1983), these are necessary conditions for the validation of the relationships. Beginning with elementary-age childre, longitudinal data to assess the causal implications seem warranted and positively supported by these findings.…”
Section: Discussionmentioning
confidence: 93%
“…A sizable portion of children, adolescents, and adults have become concerned and worried to some degree about the ever present nuclear threat (e.g., Beardslee & Mack, 1982;Escalona, 1965Escalona, , 1982Kramer, Kalick, & Millburn, 1983;Mayton, in press;Schwebel, 1963Schwebel, , 1965Schwebel, , 1982. Elder (1965) suggested that this "possibility of thermonuclear war and all the attendent cold war tensions should produce a high incidence and large variety of emotional responses'' (p. 120).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, during the Cuban missile crisis only 25% of the young people sampled felt that there would be a nuclear war, as compared to 50% immediately after the Berlin crisis. Schwebel interpreted the disparity as follows: "The heightened threat of annihilation, it seems, nourished an irrational optimism, an insistent need to believe that there would be no war, nourished, that is, a denial of the obviously greater possibility o f war" (14). Although this is an interesting and provocative interpretation, one might ask how well those young people really understood what was going on.…”
Section: Children and The Nuclear Threatmentioning
confidence: 97%
“…A child victim of parental abuse may be fearful or ambivalent of a relationship with a parent~r other adult (Kempe & Kempe, 1978). Escalona (1965) and Schwebel (1982) noted the lack of trust that many school-age children express in response to societal violence.…”
Section: Children's Response To Violencementioning
confidence: 97%